Study of Clinical Correlates of Tubercular Meningitis in a Tertiary Care Centre in Moradabad (Academia Journal of Medicine, 2020)
Background: Tuberculosis continues to remain a leading cause of mortality worldwide with tubercular meningitis being the most common  type of central nervous system tuberculosis that is associated with significant morbidity and mortality if not identified and treated promptly.  Due to meager amount of published data and lack of evaluation of the western UP population, this study was conducted in order to observe a  detailed clinical course of the disease as well as to analyze predictors of morbidity and mortality in patients of TBM admitted at a tertiary care  hospital in Moradabad.Subjects and Methods: A total of 120 patients with diagnosis of TBM as per the diagnostic criteria of the study were  included and all their information and features recorded and treatment done as per guidelines and a follow-up done at 3 months using Barthel  Index.Results: Multivariate logistic regression analysis of various factors revealed age of the patient (p=0.04), duration of symptoms  (p=0.002), stage of TBM on presentation (p=0.001), TLC>9000 (p=0.006), low CSF glucose (p=0.01), hyponatremia (p=0.04),  hypoalbuminemia (p=0.007) and hydrocephalus (p=0.04) on neuroimaging were significant risk factors of mortality and morbidity in adult  patients of TBM.Conclusion: The current study may provide components for the composition of a score to predict outcome using the  significant poor prognostic factors that were recognized in this study. This can be utilised for prompt employment of rigorous management  remedies in order to reduce patients’ morbidity and mortality.
Keywords: Tubercular Meningitis; HIV; CSF